Brivanib as adjuvant therapy to transarterial chemoembolization in patients with hepatocellular carcinoma: A randomized phase III trial. Issue 5 (29th September 2014) - Kudo, Masatoshi; Han, Guohong; Finn, Richard S.; Poon, Ronnie T.P.; Blanc, Jean‐Frederic; Yan, Lunan; Yang, Jijin; Lu, Ligong; Tak, Won‐Young; Yu, Xiaoping; Lee, Joon‐Hyeok; Lin, Shi‐Ming; et al.
<x xml:space="preserve">Abstract</x> Transarterial chemoembolization (TACE) is the current standard of treatment for unresectable intermediate‐stage hepatocellular carcinoma (HCC). Brivanib, a selective dual inhibitor of vascular endothelial growth factor and fibroblast growth factor signaling, may improve the effectiveness of TACE when given as an adjuvant to TACE. In this multinational, randomized, double‐blind, placebo‐controlled, phase III study, 870 patients with TACE‐eligible HCC were planned to be randomly assigned (1:1) after the first TACE to receive either brivanib 800 mg or placebo orally once‐daily. The primary endpoint was overall survival (OS). Secondary endpoints included time to disease progression (TTDP; a composite endpoint based on development of extrahepatic spread or vascular invasion, deterioration of liver function or performance status, or death), time to extrahepatic spread or vascular invasion (TTES/VI), rate of TACE, and safety. Time to radiographic progression (TTP) and objective response rate were exploratory endpoints. The trial was terminated after randomization of 502 patients (brivanib, 249; placebo, 253) when two other phase III studies of brivanib in advanced HCC patients failed to meet OS objectives. At termination, median follow‐up was approximately 16 months. Intention‐to‐treat analysis showed no improvement in OS with brivanib versus placebo (median, 26.4 [95% confidence interval CI: 19.1 to not reached] vs. 26.1 months [19.0‐30.9]; hazard ratio [HR]: 0.90 [95% CI: 0.66‐1.23]; log‐rank P = 0.5280). Brivanib improved TTES/VI (HR, 0.64 [95% CI: 0.45‐0.90]), TTP (0.61 [0.48‐0.77]), and rate of TACE (0.72 [0.61‐0.86]), but not TTDP (0.94 [0.72‐1.22]) versus placebo. Most frequent grade 3‐4 adverse events included hyponatremia (brivanib, 18% vs. placebo, 5%) and hypertension (13% vs. 3%). Conclusions: In this study, brivanib as adjuvant therapy to TACE did not improve OS. (Hepatology 2014;60:1697–1707)